1997
DOI: 10.1093/humrep/12.4.734
|View full text |Cite
|
Sign up to set email alerts
|

Fertilization and pregnancy using intentionally cryopreserved testicular tissue as the sperm source for intracytoplasmic sperm injection in 10 men with non-obstructive azoospermia

Abstract: Testicular tissue extraction (TESE) to obtain spermatozoa for use with intracytoplasmic sperm injection (ICSI) has recently been employed in patients with non-obstructive azoospermia. Standard protocol is to retrieve a new sample of testis tissue on the day of oocyte recovery. Unfortunately, approximately 30% of men will possess no spermatozoa in their tissue, making ICSI an impossibility. We investigated whether testicular tissue that was intentionally obtained well before any planned ICSI cycle and cryoprese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(49 citation statements)
references
References 18 publications
2
45
0
2
Order By: Relevance
“…Repeated surgery not only increases the cost but also causes inflammation to the testis, leading to testicular devascularization and fibrosis [Schlegel and Su 1997]. Also, it avoids the need for the couple to both undergo a surgical procedure on the same day [Oates et al 1997].…”
Section: Storage Methods For Small Samplesmentioning
confidence: 99%
“…Repeated surgery not only increases the cost but also causes inflammation to the testis, leading to testicular devascularization and fibrosis [Schlegel and Su 1997]. Also, it avoids the need for the couple to both undergo a surgical procedure on the same day [Oates et al 1997].…”
Section: Storage Methods For Small Samplesmentioning
confidence: 99%
“…Thus, testicular tissue cryopreservation is necessary to avoid repeat TESE for subsequent ICSI trials [Nogueira et al 1999], and successful fertilization and pregnancy have been reported using frozen-thawed testicular spermatozoa and testicular tissue [Oates et al 1997;Gianaroli et al 1999]. The fertilization rate using frozen-thawed spermatozoa from men with NOA has been shown to range from 38-70% Gil-Salom et al 1998;Wood et al 2002].…”
Section: Introductionmentioning
confidence: 99%
“…Although the use of cryopreserved testicular sperm is not easy because of their low numbers and motility [3,9], there were no differences in fertilization and pregnancy rates for fresh and thawed testicular sperm from men with OA and non-obstructive azoospermia (NOA) [10,11]. Also, fertilization and pregnancies have been reported using thawed testicular sperm and testicular tissue [12,13].…”
Section: Introductionmentioning
confidence: 99%